Implementasi Revolusi Industri 5.0 pada Pengabdian Masyarakat Bidang Teknologi di Yayasan Rumah Yatim Arrohman Lodaya - Farisi, Farhan Siddiq Al; Ahdini, Allifia; Fitriyani , Anisa; Pradeka, Deden; Juhana, Agus; Hendriyana, Hendriyana (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
In light of the swift advancement of technology, individuals are compelled to see current technological innovations as a means to enhance and maximize the overall standard of living. One potential approach to societal advancement involves achieving a harmonious equilibrium between technology and social life. Nevertheless, it is important to acknowledge that not all strata of society possess the capacity to effectively adjust to these transformations. In light of this, it is imperative to implement pedagogical strategies and instructional approaches. The instructional and educational activities were conducted at Ar-Rohman Orphanage in Bandung, serving as a means to facilitate community adaptation. This particular exercise is comprised of three distinct stages. The initial phase involves the compilation of the teaching syllabus required for the teaching and training procedures. Subsequently, the second phase encompasses the implementation of teaching and training activities, along with the assessment of participants' comprehension. Finally, the third phase entails the execution of a concluding evaluation. The pupils of Ar-Rohman Orphanage engage in community service activities that involve teaching and training. These activities enable them to effectively manage the integration of technology into their social lives, namely through fostering the development of problem-solving and critical thinking abilities.